2004
DOI: 10.1590/s0004-28032004000100004
|View full text |Cite
|
Sign up to set email alerts
|

A influência das fases oral e faríngea na dinâmica da deglutição

Abstract: The closed organization type was the one characterized as normal. The "open expanded", "prolonged" and "unstable" organization type can be associated with alteration in the swallowing process. The "lentify" and "two times" ejection types also point to swallowing physiology alteration. There are functional correlation between organization and oral ejection. The oral organization has influence, not only in the quality of the oral ejection, but also, in the effective dynamics of the pharyngeal phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
15

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 19 publications
2
19
0
15
Order By: Relevance
“…Dinâmicas musculares em indivíduos com discrepâncias esqueletais como prognatismo mandibular ilustram claramente tais situações. Eventos significativos na biomecânica em dinâmicas, como a deglutição 15 , podem necessitar de ajustes para que o sistema estomatognático mantenha-se está-vel e a função ocorra 16 . O músculo supra-hióideo é considerado estraté-gico na deglutição, pois participa de mecanismos…”
Section: Em Sujeitos Classe I E Iii De Angleunclassified
“…Dinâmicas musculares em indivíduos com discrepâncias esqueletais como prognatismo mandibular ilustram claramente tais situações. Eventos significativos na biomecânica em dinâmicas, como a deglutição 15 , podem necessitar de ajustes para que o sistema estomatognático mantenha-se está-vel e a função ocorra 16 . O músculo supra-hióideo é considerado estraté-gico na deglutição, pois participa de mecanismos…”
Section: Em Sujeitos Classe I E Iii De Angleunclassified
“…And thus swallowing can be classified as oral, pharyngeal and esophageal depending on the location of the food bolus 1 . This scheduled activity can be initiated voluntarily or synergistic awakened by movements triggered by sensory impulses from the posterior pharynx 2 . This whole process has underlying complex neurophysiological mechanisms that require the activation of 55 muscles through six pairs of cranial nerves 3 and while it may initially be either conscious or unconscious, the final phase of swallowing occurs through blood pressure changes and contractions of contractile muscles of faringe1.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a good prognosis in patients with gastrointestinal dysfunction, epidemiological studies in endemic areas have shown that malnutrition can occur with the progression of the disease 8 . The effect of Cd in the digestive tract of affected individuals influences the dynamics of swallowing and can lead to changes in nutritional status 9,10 . Adequate nutrition can reduce the risk of colon infection, especially foods with antioxidant compounds 11 .…”
Section: Introductionmentioning
confidence: 99%